Biblical portraits of creation : celebrating the maker of heaven and earth - Kaiser, Walter C.; Little, Dorington G. (Wooster : Weaver Book Company, 2014)
A faithful and edifying exposition of key chapters or sections of the Bible that speak of the glories of creation. It represents an ideal resource for pastors who want to preach a series on creation. And with its use of study questions, it can be used with profit for group Bible study. --from publisher description.
Wisdom was there before God created the world -- In the beginning God created the universe -- A garden for Adam and Eve -- A divine ode to creation -- How magnificent is God's name in all the earth -- The lord of the seven thunders -- Creation by the word of God -- The noise of heaven and earth -- Getting the facts straight about God and creation -- Jesus and the new Genesis advent -- The new heavens and the new earth -- Our new creation confidence for proclamation and living.
Includes bibliographical references and indexes.
Print version record.
Keywords: Creationism -- Biblical teaching; Creation -- Biblical teaching; Bible -- Commentaries; RELIGION / Biblical Studies / General; RELIGION / Christian Theology / General; Electronic books